A Survey of Learner-Teacher Needs for Tomorrow's Pre-academic Reading Classrooms - Mukundan, Jayakaran; Ting, Su Hie (Universiti Malaysia Sarawak, UNIMAS, 2006)
The present study evaluates the use of textbooks and materials in a preacademic reading programme in a twinning institution (Malaysia-U.S.A). The use of teaching-learning materials were evaluated by means of questionnaires.